The Price Tag of "Pay-for-Delay" - Feldman, Robin (Science and Technology Law Review, 2022)
In a landmark decision nearly a decade ago, the U.S. Supreme Court opened the door for antitrust suits against brand and generic pharmaceutical companies who engage in collusive settlements to delay the time for the generic to come to market. With these “pay-for-delay” agreements, brand-name companies offer prospective generics some form of compensation in exchange for the generic’s promise not to enter the market until an agreed-upon date. Laying the groundwork for the lawsuit that would eventually lead to the Actavis decision, the Federal Trade Commission (“FTC”) published a study estimating that pay-for-delay agreements cost American consumers 3.5 billion annually, a figure that has been cited repeatedly by scholars and policymakers alike. To understand the state of pay-for-delay agreements, this Article presents an in-depth examination of the burden that pay-for-delay imposes, both on society at large and on individual patients, and explores the modern legal landscape that has emerged since the Supreme Court’s historic pronouncement. Part I describes pay- for-delay agreements, exploring the literature on the potential harm of such agreements among pharmaceutical competitors. Part II presents a new analysis demonstrating that the cost of pay-for-delay to American consumers is far greater than anyone has recognized, and well beyond the 3.5 billion figure cited by the FTC in 2010. We applied six different methodologies to provide as fair and broad a view as possible. The range of methodologies show that at a minimum, the cost of pay-for-delay settlements on the U.S. population between 2006 and 2017 is 6.2 billion per year—almost double that of the FTC’s estimate. The methodology with the largest result suggests that the cost could be as high as 37.1 billion per year— ten times higher. Part III argues that courts are allowing this costly problem to flourish unchecked. This part reviews pay-for-delay decisions since Actavis, arguing that the courts have failed to properly analyze such cases from the perspective of all three notions inherent in the words “pay,” “for,” and “delay.” Finally, Part IV offers a path forward through the doctrinal haze.